Influence of selected environmental factors on the abundance of aerobic anoxygenic phototrophs in peat-bog lakes - Lew, Sylwia; Lew, Marcin; Koblížek, Michal (Environmental science and pollution research international, 2016)
Aerobic anoxygenic phototrophs (AAPs) are photoheterotrophic prokaryotes that are widespread in many limnic and marine environments. So far, little is known about their distribution in peat-bog lakes. Seventeen peat-bog lakes were sampled during three summer seasons 2009, 2011, and 2012, and the vertical distribution of AAPs was determined by infrared epifluorescence microscopy. The analysis demonstrated that in the surface layers of the studied lakes, AAP abundance ranged from 0.3 to 12.04 × 10(5) cells mL(-1), which represents <1 to 18.3 % of the total bacteria. The vertical distribution of AAPs confirmed their presence in the upper parts of the water column with minimum numbers in the anoxic bottom waters. We have shown that the AAP abundance was significantly positively correlated with the water pH, and the highest proportion of photoheterotrophs was found in peat-bog lakes with a pH between 6.7 and 7.6. Our results demonstrated an influence of water acidity on the abundance of AAPs, which may reflect a fundamental difference in the microbial composition between acidic and pH neutral peat-bog lakes.
Keywords: Seasons; monitorování životního prostředí; mokřady; Bacteria, Aerobic; Environmental factors; Peat-bog lakes; Environmental Monitoring; jezera; aerobní bakterie; půda; Wetlands; kyslík; mikrobiologie vody; Lakes; Aerobic anoxygenic phototrophic bacteria; pH; Water Microbiology; Oxygen; Humic and dystrophic lakes; roční období; Soil